India's Women Entrepreneurship Program Initiatives: Issues, Challenges and Opportunities - Mukta Goyal (Prosperity: Journal of Society and Empowerment, 2021)
The transformation of Indian society's social content, in terms of increased educational status for women and various ambitions for a better life, necessitated a change in the life style of Indian women. In every walk of life, she has competed with man and successfully stood up to him, and company is no exception. These female leaders are confident and willing to take risks. With their efforts, diligence, and perseverance, they were able to survive and succeed in this cutthroat rivalry. The aim of this paper is to investigate the main factors that encourage women to pursue entrepreneurial endeavors, as well as their role in growing women's entrepreneurial intentions in Indian micro, small, and medium businesses and the reasons for women's slow progress in India, suggestions for women's development, and schemes for promoting and developing women's entrepreneurship in India.  The study discovers that antecedents such as motivational influences, perceived viability, and entrepreneurial ability play a significant role in the actions of women entrepreneurs. The results have been very significant in the few cases where training has been designed and delivered. This paper will discuss the current state of women entrepreneurs in India, as well as the obstacles and problems they face in establishing and managing their businesses in a highly competitive market. Primary sources, such as published studies, essays, and academic papers, are included in this paper's conceptual design.